A Critique on the Book “the Dictionary of Sufism and Mysticism” - Mohammad Reza Movahedi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The article is a critique of the book "Dictionary of Sufism and Mysticism" by Dr. Mohammad Estelami, which has been prepared in two volumes. After expressing the good aspects of the book, some of the formal and content weaknesses of the book have been enumerated. Some of the most important weaknesses are: not mentioning the names of many earlier and later works in the research background of this work. It was necessary to provide a relatively comprehensive definition of the idiomatic meaning of the words; for example, in this dictionary, the word "water" or "dream" is considered a mystical term, although the author in the entry "water" in eight lines only says the same thing: water alone does not have a Sufi and mystical meaning. The choice of entries has an unfavorable preference for terms or concepts. Also, many mystical interpretations have been explained mainly based on the views of Rumi and Hafez Shirazi. In this critique, we have tried from three axes: the style and arrangement of the book; content and explanatory contents, and the type of sources and their learning should be seen in the present dictionary.